Reunifying Versus Living Apart Together Across Borders: A Comparative Analysis of sub‐Saharan Migration to Europe. Issue 1 (11th November 2014) - Beauchemin, Cris; Nappa, Jocelyn; Schoumaker, Bruno; Baizan, Pau; González‐Ferrer, Amparo; Caarls, Kim; Mazzucato, Valentina
Abstract : This article studies the process of reunification in Europe among "living apart together across borders" (LATAB) couples of African origin (DR Congo, Ghana, and Senegal). Couple reunion is conceived as a multilevel process, wherein state selection (through immigration policies in destination countries) interacts with self‐selection (at the couple level), under influence of the social context at origin. Based on event history analyses of the MAFE project, empirical results show that LATAB is a majority and durable living arrangement for sub‐Saharan migrants, that the odds if reunifying depend on gender and inter‐generational relationships, and that restrictive contexts at destination do not deter couple reunion.